Uruguay and its Development Forecast. Opportunities and Limitations - Gerardo Caetano; Gustavo De Armas (Íconos)
Over the past few years a number of voices – both from the political realm and academia – have reintroduced the question of whether Uruguay can “leapfrog development” in the reasonably-short term. The trend of economic wealth and the validation of various wholesome social tendencies in the recent past seem to enrich the opportunity in this question: Can Uruguay effectively sidestep what some authors have called “the middle income trap” and enter a higher stage of development? What are the important tasks that must be undertaken to go in this direction? The following text proposes several investigative leads that aim to contribute to the understanding of this crucial subject in today’s Uruguay.